The nexus between financial inclusion and financial development in Zimbabwe (2009-2015) - Moyo, Onesimo Mazai (Research of GSB, 2018)
The study aims to establish the nexus between financial inclusion and financial development in Zimbabwe covering the period from 2009 to 2015. Using descriptive statistics including correlation analysis, t-tests, and graphical analysis, the study revealed that there is a positive relationship between financial inclusion and financial development. The study however established that the relationship is relatively weak. The positive relationship is being driven by expansion of the banking sector into previously marginalised and unbanked markets, riding on the increase in financial and mobile technology based banking products. The weak relationship is explained by the current high levels of financial exclusion and the increasing levels of financial dis-intermediation occurring in Zimbabwe. This is further explained by high levels of informalisation of the economy and the deterioration in the microeconomic environment which then resulted in cash shortages and creation of quasi-currencies with the potential to further dent market confidence. People then preferred to transact outside the formal financial system. The study further established that financial inclusion, through mobile and financial technology has great potential to support financial development in Zimbabwe. This is premised on the established high mobile penetration rate and the impact that mobile and financial technology has had on financial inclusion in the short period since 2012. It is also established that the negative governance factors, (as ranked by the World Bank World Development Indicators (WDI)), such as political stability, rule of law, regulatory quality and government effectiveness had largely a strong and significant relationship with financial inclusion and financial development. These negative governance factors need to be addressed by policy makers because they have the potential to inhibit local and international trust and market confidence in Zimbabwe's financial system. The loss of trust and market confidence impacts negatively on effective execution of both financial inclusion and financial development goals. It is imperative that interventions to leverage financial development through financial inclusion must embrace developments in the financial technology and mobile technology sectors due to the high mobile penetration rate and potential to lower transaction costs and foster financial inclusion. Policy makers must devise regulatory policies that foster infrastructure sharing, interoperability and interconnectivity of MNOs mobile and financial technology platforms to increase levels of financial inclusion and financial development. The established nexus makes it imperative that a national financial inclusion strategy must be complemented by a supportive financial development strategy for optimum results.